# what is the derivative of x/tan(x) and find f'(pi/4) f'(x)=(tanx-x*sec(x)^2)/(tanx)^2 That's the quotient rule for derivatives or as my teacher says: Low,low, low D'High, minus High d'low all over low square that's the quotient rule related homework questions

• #### what is the derivative of x/tan(x) and find f'(pi/4) f'(x)=(tanx-x*sec(x)^2)/(tanx)^2 That's the quotient rule for derivatives or as my teacher says: Low,low, low D'High, minus High d'low all over low square that's the quotient rule

what is the derivative of x/tan(x) and find f'(pi/4) f'(x)=(tanx-x*sec(x)^2)/(tanx)^2 That's the quotient rule for derivatives or as my teacher says: Low,low, low D'High, minus High d'low all over low square that's the quotient rule. It's a song which helps. D'High or d'low means the derivative of the top or bottom. Anyways: the answer choices are: 2...

• #### It’s review question, I need this as soon as possible. Thank you 3) For thè diferential equation: (a) The point zo =-1 is an ordinary point. Compute the recursion formula for the coefficients of... It’s review question, I need this as soon as possible. Thank you 3) For thè diferential equation: (a) The point zo =-1 is an ordinary point. Compute the recursion formula for the coefficients of the power series solution centered at zo- -1 and use it to compute the first three nonzero terms of the power series when -1)-s and v(-1)-0. (25 points) (b) Th...

• #### Dont copié formé thé book oh ya dont copié formé thé book cause you Oiil inde up being triste soi remembré not toi copié frome thé book oh ya

Dont copié formé thé book oh ya dont copié formé thé book cause you Oiil inde up being triste soi remembré not toi copié frome thé book oh ya!translation in english please!

• #### 2 times the square root of x minus 1 minus the square root of 3x minus 5 equals the square root of x minus 9

2 times the square root of x minus 1 minus the square root of 3x minus 5 equals the square root of x minus 9

• #### If α and β are two angles in Quadrant II such that tan α= -1/2 and tan β = -2/3, find cos(α+β) Work: cos(α+β) = [ 1 - (tan α)(tan β) ] / [ 1 + (tan α)(tan β)] cos(α+β) = [ 1 - (-1/2)(

If α and β are two angles in Quadrant II such that tan α= -1/2 and tan β = -2/3, find cos(α+β)Work:cos(α+β) = [ 1 - (tan α)(tan β) ] / [ 1 + (tan α)(tan β)]cos(α+β) = [ 1 - (-1/2)(-2/3) ] / [ 1 + (-1/2)(-2/3)]cos(α+β) = [ 1 - 1/3 ] / [ 1 + 1/3 ]cos(α+β) = [ 2/3 ] / [ 4/...

• #### how does secx(tanx + tan^2x- sec^2x) simplified to sec x (tanx -1)

how doessecx(tanx + tan^2x- sec^2x)simplified tosec x (tanx -1)?

• #### what is the quotient of y minus 5 times the square root of 2y square minus 7y minus 15

what is the quotient of y minus 5 times the square root of 2y square minus 7y minus 15?

• #### Simplify 1 over 2 of 1 over 4 devide 1 over 3 all over 1 over 6 minus 3 over 4 plus 1 over 2

Simplify 1 over 2 of 1 over 4 devide 1 over 3 all over 1 over 6 minus 3 over 4 plus 1 over 2

• #### 2^2x-1 = 32^x-2 2/x - 1/2x= 1/2 (2 over x minus 1 over 2x equals 1 over 2) 3/x + 8/x-5= 1 (3 over x plus 8 over x minus 5 equals 1)

2^2x-1 = 32^x-22/x - 1/2x= 1/2 (2 over x minus 1 over 2x equals 1 over 2)3/x + 8/x-5= 1(3 over x plus 8 over x minus 5 equals 1)

• #### (1/sec 0 + tan 0) + (1/ sec 0 - tan 0 )= 2 sec 0

(1/sec 0 + tan 0) + (1/ sec 0 - tan 0 )= 2 sec 0

• #### How would you establish this identity: (1+sec(beta))/(sec(beta))=(sin^2(beta))/(1-cos(beta)) on the right, sin^2 = 1-cos^2, that factor to 1-cos * `1+cos, then the denominator makes the entire right side 1+cosB which is 1+1/sec which is 1/sec (sec+1)

How would you establish this identity: (1+sec(beta))/(sec(beta))=(sin^2(beta))/(1-cos(beta))on the right, sin^2 = 1-cos^2, that factor to 1-cos * `1+cos, then the denominator makes the entire right side 1+cosB which is 1+1/sec which is 1/sec (sec+1) qedusing sec(beta) = 1/cos(beta): 1+sec(beta))/(sec(beta))= 1 + cos(beta) sin^2(beta)/(1-cos(beta)) = (1-cos^2...

• #### Simplify this complex rational expression: 8 divided by x square minus 4x minus 21 minus 1 divided by x+3 then all of the above divided by 1 divided by x-7 plus 1 thank you :)

Simplify this complex rational expression: 8 divided by x square minus 4x minus 21 minus 1 divided by x+3 then all of the above divided by 1 divided by x-7 plus 1 thank you :)

• #### sqrt(1+tan x)-sqrt(1+sin x) lim all divided by x^3 x-->0 Use that Sqrt[1+x] = 1+ 1/2 x + 1/2 (-1/2)/2 x^2 + 1/2(-1/2)(-3/2)/6 x^3 + O(x^4) You can thus write the numerator as: 1/2 [tan(x) - sin(x)] - 1/8 [tan^2(x) - sin^2(x)] + 1/16 [tan^3(x)

sqrt(1+tan x)-sqrt(1+sin x) lim all divided by x^3 x-->0 Use that Sqrt[1+x] = 1+ 1/2 x + 1/2 (-1/2)/2 x^2 + 1/2(-1/2)(-3/2)/6 x^3 + O(x^4) You can thus write the numerator as: 1/2 [tan(x) - sin(x)] - 1/8 [tan^2(x) - sin^2(x)] + 1/16 [tan^3(x) - sin^3(x)] + O(x^4) Note that sin(x) and tan(x) are of order x near x = 0 so that the neglected terms are of orde...

• #### solve each identity algebraically 1)(1-tanx)/(1-cotx)=-tanx 2)(1+cotx)/(1+tanx)=cotx

solve each identity algebraically1)(1-tanx)/(1-cotx)=-tanx2)(1+cotx)/(1+tanx)=cotx

• #### Proving identity (sinx+tanx)/(cosx+1)=tanx RS: (sinx+(sinx/cosx))/(cosx+1) ((sinxcosx/cosx)+(sinx/cosx))x 1/(cosx+1) sinx(cosx+1)/cosx x 1/(cosx+1) sinx/cosx = tanx RS = LS How did sinxcosx/cosx turn to sinx(cosx+1)

Proving identity(sinx+tanx)/(cosx+1)=tanxRS: (sinx+(sinx/cosx))/(cosx+1)((sinxcosx/cosx)+(sinx/cosx))x 1/(cosx+1)sinx(cosx+1)/cosx x 1/(cosx+1)sinx/cosx = tanxRS = LSHow did sinxcosx/cosx turn to sinx(cosx+1)?

• #### 8. (a) (5pt) Prove the identity: cscx -cos x=sec x . sin'x 4 and tan θ<0 (b) (5pt) Find cos θ , if sin θ 8. (a) (5pt) Prove the identity: cscx -cos x=sec x . sin'x 4 and tan θ 8. (a) (5pt) Prove the identity: cscx -cos x=sec x . sin'x 4 and tan θ<0 (b) (5pt) Find cos θ , if sin θ 8. (a) (5pt) Prove the identity: cscx -cos x=sec x . sin'x 4 and tan θ

• #### Eliminate the parameter to find a Cartesian equation of the curve. Then sketch the curve and be sure to indicate the direction of the curve. x = tan(θ)+ sec(θ) , y = tan(θ)-sec(θ)

Eliminate the parameter to find a Cartesian equation of the curve. Then sketch the curve and be sure to indicate the direction of the curve. x = tan(θ)+ sec(θ) , y = tan(θ)-sec(θ)

• #### Prove that Cot(theta)/1-Tan(theta) + Tan(theta)/1-Cot(theta) = 1+Tan(theta)+Cot(theta) must show step by step I have tried a couple of steps by changing Cot to 1-1/Cot(theta) and 1-Tan(theta) 1-1/Cot (theta)

Prove that Cot(theta)/1-Tan(theta) + Tan(theta)/1-Cot(theta) = 1+Tan(theta)+Cot(theta) must show step by step I have tried a couple of steps by changing Cot to 1-1/Cot(theta) and 1-Tan(theta) 1-1/Cot (theta)

• #### 6 over x squared minus 8x = 1 over x + 3 over x squared minus 8x

6 over x squared minus 8x = 1 over x + 3 over x squared minus 8x

Need Online Homework Help?